PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK MODEM CDMA EVDO SMART TELECOM - Tedy Ardiansyah (UNIVERSITAS INDRAPRASTA PGRI, 2015)
This study aimed to analyze the effect of mareketing mix on purchase descision. The concepts of marketing mix were taken from various sources. This study is descriptive and quantitative in nature. Both primary and secondary data were employed. Secondary data were obtained from books, journals, and website. Primary data were obtained using questionnaire, which was distributed to the consumers of CDMA EVDO modem. Total responses of 100 were obtained.The classic assumption test which include heterocedastisity, normality, multicollinearity and autocorrelation, and linear regression analysis, t test and f test were employed. Based on linear regression analysis, it was found that product and channel distribution significantly influence the purchase decision. In addition products, pricing, promotion and distribution simultaneous had effects on purchase decision of Smart Telecom CDMA EVDO Modem.